Jangnāma-yi Kishm wa Jarūnnāma - Qadri, (Miras Maktoob, ISBN: 9789004365452., 2019)
For over a hundred years, between 1507 and 1622, the island of Hormuz in the Persian Gulf was in the hands of the Portuguese. It was only under Shāh ʿAbbās I that the Safavids were able to recapture Hormuz and the neighbouring island of Qishm, under the leadership of general Imām Qulī Khān and with the unexpected help of some forces of the British East India Company that happened to be in the area at the time. The two epic poems from the 11th/17th century published in this volume, one by an otherwise unknown 'Qadrī' and the other by an anonymous author, deal with the recapture of Qishm and Hormuz under Imām Qulī Khān. While not of high literary quality, the poems show some interesting local and historical features, especially the longer one on Hormuz whose author had a great admiration of Imām Qulī Khān, whom he appears to have known personally.